Analisis Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Pada PT. Phapros Tbk. - Yuyun Istiqomah; M. Rimawan M. Rimawan; Hanifah Muthiah (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of financial ratios on profit growth at PT. Phapros Tbk. The financial ratio variables used include Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO). This research employs a quantitative approach with secondary data from the company's annual financial statements for the period 2014–2023. Data analysis was conducted using multiple linear regression to examine both partial and simultaneous effects of the variables. The results show that NPM has a significant partial effect on profit growth, while DER and TATO do not have a significant partial effect. Simultaneously, all three independent variables significantly influence profit growth. These findings indicate that profitability is the dominant factor in the company's profit growth and can serve as a reference for management in formulating more effective financial strategies, as well as for investors in making investment